Hisab Hakiki Model Muhammad Wardan: Sebuah Penelusuran Awal - Susiknan Azhari (Al-Jami'ah: Journal of Islamic Studies, 2004)
This article tries to study about calculation (ḥisāb) model developed by Muhammad Wardan to formulate a National Hijriyah Calendar. Muhammad Wardan is one of the designer of the concept of wujūdul hilāl. This concept was built by combining normative and empirical level (middle way) between the system of hisab ijtima' qabla al-ghurūb and imkān al-ru'yah. This combination was also named as middle way between pure hisab and pure rukyat. Due to this type of concept, be renewal thought of Mubammad Wardan to decide the beginning of Qamariyah month was quite original at that time. Therefore, Wardan's theory of wujudūl hilāl is still used until nowadays especially by Muhammadiyah people. However, it is significant to note that the thought of Wardan does not perfectly answer  the problem of National Hijriyah Calendar, I.e., to decide the Westest and Eastest  points of a region or country to start or end the month of Ramadlan.